Effect of pregnancy on forage intake and utilization in spring-calving beef heifers wintered on flint hills range - Vanzant, E.S.; Cochran, R.C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Six ruminally and eight bi-fistulated (ruminal and esophageal), 2-yr-old beef heifers were used to study the effects of pregnancy on forage intake and utilization under grazing conditions. During the third trimester of gestation, pregnant heifers ate more (P<.05) forage than nonpregnant heifers and maintained similar (P>.10) levels of organic matter and fiber digestibility. As calving neared, pregnant animals had higher (P<.05) rates of passage and tended to have lower ruminal capacity •(P=.15) and digesta fill (P=.14) than nonpregnant animals. Differences in quality of diet selected by the two groups were minimal.
Keywords: Beef; Heifers; Pregnancy; Intake; Digestibility; Winter range